Shrimps in the mangrove - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Mangroves have been back in the international spotlight recently thanks to the protective role they played during the tsunami, which devastated coastal areas of the Indian Ocean in December 2004. Unfortunately though, many mangroves had already been lost